2017
DOI: 10.1111/1750-3841.13745
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Green Tea Polyphenols Consumption in Middle‐aged Ovariectomized Rat Model

Abstract: The present work evaluates chronic safety in middle-aged ovariectomized rats supplemented with different dosages of green tea polyphenols (GTP) in drinking water. The experiment used 6-month-old sham (n=39) and ovariectomized (OVX, n=143) female rats. All sham (n=39) and 39 of the OVX animals received no GTP treatment and their samples were collected for outcome measures at baseline, 3 months, and 6 months (n=13 per group for each). The remaining OVX animals were randomized into 4 groups receiving 0.15%, 0.5%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The potential health effects of long-term GTP consumption via drinking water by middle-aged ovariectomized SD rats were evaluated. Results on the chronic safety and clinical observations of the rats supplemented with GTP has been reported recently [30]. This study, focused on the gut microbiota, successfully evaluated both functional genomic and microbial compositional alterations of gut microbiota at two different sampling times, using next-generation sequencing (NGS) technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential health effects of long-term GTP consumption via drinking water by middle-aged ovariectomized SD rats were evaluated. Results on the chronic safety and clinical observations of the rats supplemented with GTP has been reported recently [30]. This study, focused on the gut microbiota, successfully evaluated both functional genomic and microbial compositional alterations of gut microbiota at two different sampling times, using next-generation sequencing (NGS) technologies.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted concurrently with a recently published study of the chronic toxicity and tolerance of GTP extracts (decaffeinated) among middle-aged ovariectomized rats, in which the experimental design and procedures on chemicals and animal preparations were described [30]. This rat model was developed to evaluate the beneficial effects of long-term GTP supplementation to postmenopausal women.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it is paramount to validate the most promising in vitro data using in vivo models, like toxicologically treated [54,87] or disease-specific [51,56] rodents that could be fed with the original foods, extracts, or isolated bioactive polyphenol molecules. This is also fundamental in assessing the in vivo side effects of polyphenols, particularly in situations mentioned above, and to ascertain the safe usage of any proposed polyphenol [88][89][90][91]. Ultimately, results of in vitro studies, as well as those from animal models, have to be validated by a human pilot study where the beneficial vs. deleterious effects can be monitored, eventually proceeding to clinical trials [92].…”
Section: Neurotoxicity Vs Neuroprotectionmentioning
confidence: 99%
“…Of these, some studies state that the regular consumption of green tea and green-tea extracts seem to be safe [88], particularly in the form of the traditional infusion [91,103], but the use of concentrated extracts with doses of individual constituents, consumed in solid dosage form, may need additional As stated before, few studies are focused on the toxicity or safety of consuming polyphenols. Of these, some studies state that the regular consumption of green tea and green-tea extracts seem to be safe [88], particularly in the form of the traditional infusion [91,103], but the use of concentrated extracts with doses of individual constituents, consumed in solid dosage form, may need additional study to guarantee their safe use [89]. The direct administration of moderate doses of resveratrol seem to be safe and cardioprotective [104].…”
Section: Safety In the Polyphenol Worldmentioning
confidence: 99%
“…For example, in a rodent study, Sayama and co-workers [ 38 ] found that green tea lowered triacylglycerol (TAG) levels but did not change TC concentrations. The previous study has shown that the severity of EGCG induced toxicity seems to be a function of dose, administration route and period of treatment [ 39 , 40 ]. Dietary dosages of green tea extract can improve lipid profile and insulin sensitivity and change the genes expression involved in the homeostasis of glucose and lipid [ 41 ].…”
Section: Discussionmentioning
confidence: 99%